Optimization of Adsorption Parameters for Removal of Cationic Dyes on Lignocellulosic Agricultural Waste Modified by Citric Acid: Central Composite Design - Liudmyla Soldatkina; Marianna Yanar (ChemEngineering, 2023)
Barley straw (BS-C) and corn stalks (CS-C) modified by citric acid are hopeful adsorbents for the removal of cationic dyes from aqueous solutions. Optimization of adsorption factors to improve removal of methylene blue (MB) and malachite green (MG) on BC-C and CS-C was carried out by response surface methodology with central composite design. The effect of pH, time, dye concentration, and adsorbent dose on the removal efficiency of cationic dyes was investigated. The experimental data were in good agreement with the predicted data obtained by mathematical models. Accordingly, the maximum MB removal efficiency on BS-C of 97% was achieved with a pH of 6.4, time of 50 min, an adsorbent dose of 11 g L−1, and an initial MB concentration of 26 mg L−1; the maximum MG removal efficiency on BS-C of 95% was achieved with a pH of 7.2, time of 60 min, an adsorbent dose of 14 g L−1, and an initial MG concentration of 24 mg L−1; the maximum MB removal efficiency on CS-C of 97% was achieved with a pH of 6.5, time of 45 min, an adsorbent dose of 11 g L−1, and an initial MB concentration of 20 mg L−1; the maximum MG removal efficiency on CS-C of 94% was achieved with a pH of 6.6, time of 50 min, an adsorbent dose of 12 g L−1, and an initial MG concentration of 24 mg L−1.